Castleman disease versus generalized tuberculosis: a case of fever of unknown origin - Niño-Morin, Edgard (2022)
We present the case of a 25-year-old woman with fever of unknown origin, whose cervical node biopsy study was reported as Castleman disease, but who at follow-up turned out to be multisystem tuberculosis. He received antituberculous treatment with good clinical and laboratory evolution at follow-up. It is emphasized that, in the face of diseases of low prevalence, such as Castleman disease, tuberculosis should be ruled out in countries like ours.